2012
DOI: 10.3310/hta16270
|View full text |Cite
|
Sign up to set email alerts
|

Mode of data elicitation, acquisition and response to surveys: a systematic review.

Abstract: How to obtain copies of this and other HTA programme reports An electronic version of this title, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable DVD is also available (see below).Printed copies of HTA journal series issues cost £20 each (post and packing free in the UK) to both public and private sector purchasers from our despatch agents.Non-UK purchasers will have to pay a small fee for post and packing. For Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 96 publications
2
29
0
2
Order By: Relevance
“…There is evidence that single-item measures are more likely to be biased than multiquestion measures. 117 We do not feel that the results for the other questionnaires are likely to be biased.…”
Section: Main Analysismentioning
confidence: 95%
“…There is evidence that single-item measures are more likely to be biased than multiquestion measures. 117 We do not feel that the results for the other questionnaires are likely to be biased.…”
Section: Main Analysismentioning
confidence: 95%
“…Several studies have reported greater underestimation of weight (and BMI) with remote SR collection methods than with face-to-face interviews (Hood et al 2012). However, we observed a good agreement between the BMI classifications derived from SR and measured height and weight (j = 0.939), with just six participants being wrongly classified when SR data were used.…”
Section: Concordance Of Bmi Classificationmentioning
confidence: 99%
“…There is evidence from the MODE-ARTS systematic review that pragmatic changes of administrator 'at random' are unlikely to bias outcomes within placebo-controlled trials. 167 …”
Section: Mode Of Data Collectionmentioning
confidence: 99%